(untitled) (Research, Society and Development, 2025)
This study aimed to review and synthesize scientific evidence on the influence of psychosocial factors, such as social support, resilience, self-efficacy, and mental health, on the preservation of functional capacity in older adults, promoting healthy aging. A scoping review was conducted using articles published between 2020 and 2024, retrieved from the Medline via PubMed and Cochrane Library databases. The search strategy employed descriptors related to psychosocial factors and functional capacity in older adults, including quantitative studies, qualitative studies, and systematic reviews. Articles not peer-reviewed and those focused exclusively on biomedical aspects were excluded. The review identified 15 studies highlighting social support, mental health, and resilience as essential factors in maintaining functional capacity. Support networks significantly reduced the risk of functional decline, while chronic stress and depression were associated with functional deterioration. Self-efficacy and a positive perception of health emerged as crucial protective factors. The findings reinforce the importance of integrating psychosocial factors into public policies targeting older adults. Interventions focused on strengthening support networks and promoting mental health may contribute to the preservation of functionality and quality of life in older adults. Future research should focus on personalizing these interventions and evaluating their longitudinal impacts.